Intelligent regulation as an alternative to administrative normativism: A new paradigm of lawmaking in Kazakhstan - Alimkulov Е.Т.; Safinov К.Б.; Akhatov У.А. (BULLETIN of L.N. Gumilyov Eurasian National University Law Series, 2026)
The article examines the problem of transforming lawmaking in the Republic of Kazakhstan in the context of the digitalization of public administration and the development of artificial intelligence technologies. It substantiates that the existing model of administrative normativism, focused on excessive detail of legal regulation, leads to legislative inflation, fragmentation of the regulatory framework, conflicts, and a decrease in the effectiveness of law enforcement. The aim of the study is to provide a theoretical justification for the transition to a new paradigm of intelligent regulation based on a principles-oriented approach, evidence-based policy, and the digital infrastructure of law. The article shows that the modernization of legislation should include a fundamental cleanup of the regulatory framework, the introduction of a "regulatory guillotine" mechanism, the formation of a unified database of legal definitions, the use of artificial intelligence as an analytical tool for lawmaking, and the mandatory application of regulatory impact assessment. It is concluded that intelligent regulation acts not only as a technological innovation but also as a new model of legal policy aimed at increasing the flexibility, consistency, transparency, and effectiveness of the legislation of the Republic of Kazakhstan.